2016
DOI: 10.5966/sctm.2015-0300
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Coinjection and Distant Injection of Mesenchymal Stem Cells on Breast Tumor Cell Growth

Abstract: Mesenchymal stem cells (MSCs) usually promote tumor growth and metastasis. By using a breast tumor 4T1 cell-based animal model, this study determined that coinjection and distant injection of allogeneic bone marrow-derived MSCs with tumor cells could exert different effects on tumor growth. Whereas the coinjection of MSCs with 4T1 cells promoted tumor growth, surprisingly, the injection of MSCs at a site distant from the 4T1 cell inoculation site suppressed tumor growth. We further observed that, in the distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 47 publications
(59 reference statements)
2
28
0
Order By: Relevance
“…Most experimental data show that the administration of MSCs in oncological and autoimmune diseases results in MDSC accumulation and immunosuppression mediated by certain chemokines and growth factors [63][64][65]. On the other hand, when modeling cancer in mice, a dependence of the immunomodulatory "phenotype" of MSCs on the injection site was found: the simultaneous injection of MSCs with tumor cells led to immunosuppression, distal injection led to immunostimulation; the immune response was shown to correlate with a decrease in the proportion of MDSCs and T-regulatory cells (Treg) [66]. Thus, one of the mechanisms of stimulation of the innate and adaptive immune response to naïve and modified MSCs in our experiments may be the suppression of MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental data show that the administration of MSCs in oncological and autoimmune diseases results in MDSC accumulation and immunosuppression mediated by certain chemokines and growth factors [63][64][65]. On the other hand, when modeling cancer in mice, a dependence of the immunomodulatory "phenotype" of MSCs on the injection site was found: the simultaneous injection of MSCs with tumor cells led to immunosuppression, distal injection led to immunostimulation; the immune response was shown to correlate with a decrease in the proportion of MDSCs and T-regulatory cells (Treg) [66]. Thus, one of the mechanisms of stimulation of the innate and adaptive immune response to naïve and modified MSCs in our experiments may be the suppression of MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A provocative new idea to explain the dichotomy between the pro- and antitumor effects of MSCs may depend not only on how they recruit components of the immune system but on their localization within the body when the tumor first starts to develop. A recent study showed opposite effects on breast tumor growth when MSCs were coinjected or injected distantly [ 80 ]. Interestingly, in a 4T1 model of breast tumor development, the only variation was the site of injection of MSCs, demonstrating opposite effects on tumor growth for the first time in the same animal model ( Figure 6 ).…”
Section: The Interaction Of Mscs and The Immune System In The Tumomentioning
confidence: 99%
“…Treg and myeloid-derived suppressor cells (MDSC) were decreased significantly; CD8 T cells and APC were increased as a trend (although not significantly). Gene expression profiles of immune cells in the spleen and cytokine analyses of serum suggested that upregulation of TNF, IFN γ , TLR3, and IL-12 might explain the antitumor activity of distantly injected MSCs [ 80 ]. These interesting findings suggest that naïve MSCs are a double-edged sword in the modulation of tumor growth.…”
Section: The Interaction Of Mscs and The Immune System In The Tumomentioning
confidence: 99%
“…Zheng et al . 15 showed that in the 4T1 BALB/c model, distal injection of mouse BM MSCs resulted in a reduction in subcutaneous (SubQ) tumor growth, angiogenesis and lung metastasis, whereas co-injection resulted in an increase in tumor growth and angiogenesis. However, they were not able to observe the same effect in nude mice, suggesting a possible role for T cells in mediating these anti-cancer effects.…”
Section: Introductionmentioning
confidence: 99%